Does breastfeeding protect children from COVID-19? An observational study from pediatric services in Majorca, Spain - Sergio Verd; Jan Ramakers; Isabel Vinuela; Maria-Isabel; Aina Prohens; Ruth Díez (BMC, 2021)
Abstract Background It has been demonstrated that children who had been breastfed remain better protected against various infections, and notably respiratory tract infections, well beyond infancy. Since the role of breastfeeding to explain why children are less affected by COVID-19 has not been studied until now, the aim of this study was to determine whether any history of breastfeeding reduces the incidence rate of COVID-19 in children. Methods This was a secondary analysis of an observational study on clinical and epidemiological characteristics of pediatric COVID-19 in Majorca. A total of 691 children were recruited during the 5 months of August-December 2020. Eligible participants were children under 14 who were tested for SARS-CoV-2 in pediatric emergency services. The independent explanatory variable was any breastfeeding. Bivariate analyses were conducted through the Chi-square test, the Fisher's Exact test or the Student's T test. All children had the same demographic, epidemiological and clinical data collected through a study team member interview and via the participants medical records. Results Within the sample of children who visited emergency services with symptoms of potential COVID-19, we found higher prevalence of positive SARS-CoV-2 RT-PCR test results among those who were exclusively formula fed compared with those who were ever breastfed (OR 2.48; 95% CI 1.45, 3.51; P = 0.036). Conclusions The present study suggests that ever breastfeeding reduces the risk of COVID-19 among children, as documented for other infections.